THE HIPPIES IDENTITY IN THE 1960S AND ITS AFTERMATH - Nafisatul Lutfi (Rubikon : Journal of Transnational American Studies, 2015)
The study on the hippies is abundant in numbers but not many of them study the disposition and identification of the hippies during the 1960s and its aftermath. Pierre Bourdieu’s theory on cultural practice, theory of hybridity, and globalization are used in this research to investigate the disposition and trans-nationality of the hippies in order to search for their universal identity. A Transnational American Studies approach is implemented to cover the following issue: (1) the socio-cultural disposition of the hippies in the 1960s, (2) the influence of European movement to the American Hippies, (3) the cultural hybridity of the hippies in relation with India, and (4) the similarities of the hippies and the reasons behind it. This research used library research and document analysis method in gathering the data whereas descriptive analysis approach is also used to analyze the data. The United States of America, India and Germany are the three countries being studied in relation to the hippies in the 1960s. The finding shows similar dispositions or background among the hippies in some countries being studied as well as some similarities and differences in the cultural practices of the hippies in the countries being studied. This shows the transnationality of the hippie’s identity and the influence of hybridity and globalization which causes the shifting of ideology and cultural practices of the hippies in its developments.Keywords: hippies, identity, Pierre Bourdieu, habitus, hybridity, globalization, TransnationalAmerican Studies